(untitled) (World Bulletin of Management and Law, 2024)
In today’s global economic environment, most companies operate in conditions of uncertainty, unpredictability. The unstable political and socioeconomic situation in the country increases the degree of risk of decisionmaking and the functioning of enterprises in general. In such conditions the problem of ensuring the economic security of the enterprise becomes relevant. This determines the relevance of studying the issue of economic security of enterprises in modern conditions.